Effect of chewing gum in bowel preparation for patients undergoing small bowel and colon capsule endoscopy: Systematic review with meta-analysis - Jensen, Sofie Sajan; Deding, Ulrik; Hansen, Lea Østergaard; Koulaouzidis, Anastasios; Bjørsum-Meyer, Thomas (Endoscopy International Open, 2024)
Background and study aims Quality of bowel preparation and successful transit are critical factors for complete small bowel capsule endoscopy (SBCE) and colon capsule endoscopy (CCE). The aim of this systematic review with meta-analysis was to assess the impact of chewing gum as part of the bowel preparation regimen on the completion rate in both SBCE and CCE.Methods A systematic literature search was conducted in PubMed, Cochrane, Web of Science and Embase. Data were extracted upon quality assessment of included studies. Two reviewers conducted the screening process according to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis. Eighty-four studies met the search criteria and four randomized controlled trials were included in the meta-analysis, these were assessed for bias using Minors. Pooled completion rate of SBCE studies was defined as the primary outcome.Results Three randomized controlled trials were SBCE studies and one was a CCE study. The pooled completion rate (91%) was not significantly higher in SBCE patients who were given chewing gum after capsule ingestion compared to those who were not (85%). Variance information was not reported in all studies, and therefore, pooled transit time estimates could not be calculated.Conclusions Chewing gum has a good safety profile but has only been used as a booster in one CCE study and a few SBCE studies. More prospective randomized controlled trials, therefore, are needed to investigate the efficacy of chewing gum for achieving complete capsule examination.
Keywords: Endoscopy Small Bowel; Capsule endoscopy; Quality and logistical aspects; Preparation; Endoscopy Lower GI Tract